Study of Z boson pair production in e+e- collisions at LEP at √s = 189 GeV - Dova, María Teresa (1999)
The pair production of Z bosons is studied using the data collected by the L3 detector at LEP in 1998 in e+e- collisions at a centre-of-mass energy of 189 GeV. All the visible final states are considered and the cross section of this process is q0.15 measured to be <mtext>0.74</mtext>+0.15−0.14<mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>(</mtext><mtext>stat.)</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>±0.04</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>(</mtext><mtext>syst.)</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>pb</mtext>. Final states containing b quarks are enhanced by a dedicated selection and their production cross section is found to be <mtext>0.18</mtext>+0.09−0.07<mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>(</mtext><mtext>stat.)</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>±0.02</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>(syst.)</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>pb</mtext>. Both results are in agreement with the Standard Model predictions. Limits on anomalous couplings between neutral gauge bosons are derived from these measurements.